2014
DOI: 10.1073/pnas.1317041111
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing thyroid hormone signaling preserves cone photoreceptors in mouse models of retinal degeneration

Abstract: Cone phototransduction and survival of cones in the human macula is essential for color vision and for visual acuity. Progressive cone degeneration in age-related macular degeneration, Stargardt disease, and recessive cone dystrophies is a major cause of blindness. Thyroid hormone (TH) signaling, which regulates cell proliferation, differentiation, and apoptosis, plays a central role in cone opsin expression and patterning in the retina. Here, we investigated whether TH signaling affects cone viability in inhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 38 publications
(49 reference statements)
2
79
0
2
Order By: Relevance
“…It would be interesting to maintain the animals on T3 for longer periods to determine if longer treatment can result in complete reversal of S opsin gradient. However, high levels of T3 can also affect cone survival and overall affect the health of the animals (Ma et al, 2014). Nonetheless, our data demonstrates that T3 supplementation can partially reverse the cone opsin phenotype resulting from Bmal1 deletion.…”
Section: Resultsmentioning
confidence: 99%
“…It would be interesting to maintain the animals on T3 for longer periods to determine if longer treatment can result in complete reversal of S opsin gradient. However, high levels of T3 can also affect cone survival and overall affect the health of the animals (Ma et al, 2014). Nonetheless, our data demonstrates that T3 supplementation can partially reverse the cone opsin phenotype resulting from Bmal1 deletion.…”
Section: Resultsmentioning
confidence: 99%
“…Rpe65 -/-and cpfl1 mice show rapid and severe cone death. Suppressing TH signaling with anti-thyroid drugs significantly improved cone survival in these mice (Ma et al 2014). It is worth mentioning that anti-thyroid treatment does not cause rod degeneration, although T3 treatment or deletion of DIO3 has been shown to reduce rod numbers (Ng et al 2010;Ma et al 2014).…”
Section: Dio3mentioning
confidence: 94%
“…Studies using Cngb3 −/− and Gucy2e −/− mice, models of retinal degeneration, also demonstrated that stimulating TH signaling by T3 treatment deteriorates cones (Ma et al 2014).…”
Section: Dio3mentioning
confidence: 96%
See 2 more Smart Citations